GENDER ROLES IN TRADITIONAL FISH PROCESSING BUSINESS IN SMALL ISLANDS IN MALUKU - Apituley, Yolanda Marla Tania Nangkah; Nanlohy, Hellen; Rieuwpassa, Fredrik; Tapotubun, Alfonsina Marthina; Matrutty, Theodora Elsje Adelheid Agustin (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2025)
Traditional fish processing businesses represent a vital livelihood and economic sector in Maluku’s small islands. Understanding the precise allocation of gender roles within these enterprises is crucial for enhancing family economic resilience and developing effective sectoral policy. This research aims to analyze gender roles in traditional fish processing businesses. A sample of 24 fish processing business units was drawn purposively from several smoked fish processing places in Ambon City, dried fish in Eastern Seram Regency (Geser) and salted fish in Central Maluku Regency (Perigi). The data obtained was analyzed descriptive quantitatively. The research results show that activities in each traditional fish processing business can be divided into pre-production, production, and post-production stages, with the number of activities in each stage varying. In the smoked fish business, women and men collaborate significantly in the pre-production and production stages. In contrast, in post-production activities, women have significant roles in selling the products. In the dried and salted fish business, pre-production and production activities are mainly carried out by women, while men carry out post-production activities. Most of the men in the village who produce dried and salted fish earn their living as fishermen, so pre-production and production activities are carried out by women during the day when their husbands are at sea. The smoked fish produced is generally sold locally around the production site, while dried and salted fish are sold outside the island and the province.